(untitled) (Research, Society and Development, 2022)
Microcephaly is a neurological condition, in which the bearer has the head circumference below the parameters for his age group pre-established by the Ministry of Health. Gestational age and the etiology of the disease highly interfere in the sequelae of microcephaly, which can generate serious impairments in the central nervous system, such as cerebral palsy, epilepsy, intellectual disability, anomalies in the auditory and visual system, which result in several behavioral disorders in its carriers. In contrast to these needs, the Ministry of Health has developed programs for monitoring and multidisciplinary support for patients, extending to the family. Research developed in order to verify if all programs proposed by the government to children and their caregivers, since the beginning of the outbreak in Pernambuco, were provided, as well as to identify the main difficulties faced by caregivers of these children from 2015 to the end of 2015. gift. After carrying out the data collection together with the spouses, it was observed that adjustments are needed in order to improve the care and treatment of children and that there is a certain decline related to information about microcephaly. It is understood that it is important to create new government projects that ensure their rights to a good quality of life for these patients and their relatives. There is an extreme need for more investment in the area of research and dissemination of information to the population on the topic addressed.